Long-term outcomes and patterns of failure after empiric SBRT for presumed early-stage lung tumors - El-Marouk, Karim; Degerli, Esra; Käsmann, Lukas; Kröninger, Sophie; Kauffmann-Guerrero, Diego; Tufman, Amanda; Reinmuth, Niels; Duell, Thomas; Manapov, Farkhad; Belka, Claus; Eze, Chukwuka; Mansoorian, Sina (Frontiers in Oncology, 2025)
BackgroundStereotactic body radiation therapy (SBRT) is the established standard of care for medically inoperable early-stage non-small cell lung cancer (ES-NSCLC). When a biopsy is unfeasible, it is often delivered empirically, yet long-term outcomes and failure patterns remain underreported.MethodsA total of 56 patients with clinically staged T1–T3N0M0 lung tumors treated with empiric SBRT (2011–2022) were retrospectively analyzed. Nineteen patients with recurrence were assessed for failure patterns and survival. Overall survival (OS), progression-free survival (PFS), local failure-free survival (LFFS), regional failure-free survival (RFFS), and distant metastasis-free survival (DMFS) were estimated using the Kaplan–Meier method. Competing risk analysis was performed with death treated as a competing event.ResultsAt a median follow-up of 80.4 months (95% CI: 65.2–95.6), 17 patients (30.4%) were alive. Median PFS and OS were 28.5 months (95% CI: 16.4–40.8) and 41.7 months (95% CI: 14.0–69.4), respectively. LFFS was 84.1% at 5 years and 67.3% at 10 years, RFFS was 64.7% at 5 years and 58.8% at 10 years, and DMFS was 62.4% at 5 years and 56.1% at 10 years. Pathologic confirmation of recurrence was obtained in 10 patients, identifying NSCLC in six, small cell lung cancer in three, and urothelial carcinoma in one. Local failures were infrequent and occurred early (median 8.3 months), whereas regional and distant recurrences occurred later (median 13.5 and 22.8 months). At 10 years, the estimated cumulative incidence function was 6.3% for local failure, 14.8% for regional failure, 16.6% for distant failure, and 55.8% for death.ConclusionEmpiric SBRT provides durable local control in presumed early-stage NSCLC, but outcomes are limited by comorbid mortality and systemic progression. These findings emphasize its effectiveness as a local therapy and the need for prolonged surveillance and systemic strategies.